Painting the Game - MacLachlan, Patricia (New York : Margaret K. McElderry Books, 2024)
"Lucys father is a minor league baseball player, a professional pitcher hoping to get called up to the majors, and Lucy inherited his passion for the game. But shes never played pitcher. She worries her skills would be compared to her dads and shed never measure up. And his pitching may mean big things for his career and their family, but its also what keeps him away from home so much of the year. ... This summer, Lucy wants to learn to throw the perfect knuckleball"--
Keywords: Baseball for children -- Juvenile fiction; Minor league baseball -- Juvenile fiction; Pitchers (Baseball) -- Juvenile fiction; Athletic ability -- Juvenile fiction; Self-confidence in children -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Minor league baseball -- Fiction; Pitchers (Baseball) -- Fiction; Athletic ability -- Fiction; Self-confidence -- Fiction; Fathers and daughters -- Fiction; Juvenile fiction